Computational modelling of reactive processes in lithium-metal batteries - Arguello, Marcos Exequiel (Curtin University, 2022)
This Thesis presents a computational phase-field model to describe the electrodeposition process that forms dendrites within lithium-metal batteries. We describe the evolution of a phase field, the lithium-ion concentration, and electric potential during a battery charge cycle. We simulate three-dimensional spike-like lithium structures in agreement with experimentally-observed dendrite growth rates and morphologies reported in the literature. This work constitutes a relevant step towards physical-based, quantitative models needed to achieve the commercial realisation of lithium-metal batteries.